International and Macedonian Endeavours, Obstacles and Solutions Regarding Citizens’ Participation of Roma at Local Level - Dimitrovska, Milka (Центар за научно-истражувачка дејност на Правен факултет, Универзитет „Св. Климент Охридски“ - Битола, 2020)
Equality in terms of equal opportunities for every person or group of individuals, including prohibitory regulations regarding discrimination, is of immense importance of contemporary complex societal, legal and political mechanisms. The Roma are among the permanent vulnerable categories both in Europe and in the Republic of North Macedonia as far as exercising human rights is concerned. Therefore, the legal and political mechanisms protecting the Roma rights require consistent and long-term attention and improvement, which this paper attempts to provide. Namely, the paper aims to identify the legal basis for protection, but also the obstacles posed by universal, European and Macedonian legislature regarding the Roma rights and to introduce solutions for boosting citizens’ participation of the Roma at local level. Even though the existing legislative basis covers vast area, certain new possibilities within the legal and political system could be unraveled, dominantly by using the method of qualitative contents analysis of legal acts, strategic documents and empirical studies, thus concluding solutions that comply both with strategic ‘top-down’ policy making and ‘bottom-up’ measures and specific actions. This legislative and policy analysis comes to the conclusion that the continuity of affirmative action including the indispensable census, affirmative action concerning the municipalities with Roma inhabitants, targeted approach and changes in the primary school boards is needed that would benefit local government policy making subjects, experts and civil activists in the field of protection and development of human rights.
Keywords: Roma political rights, equality, local government, affirmative action, policy making